CLUSTERING WILAYAH DI PROVINSI SULAWESI UTARA BERDASARKAN KARAKTERISTIK SOSIAL EKONOMI TAHUN 2017 - Agustina Riyanti (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2018)
Abstract. Regional Medium-Term Development Plan (RPJMD) is a derivative of a medium-term national development planning system that developed based on based on the potential and advantages of the area. The alleviation of poverty and unemployment as well as improving the quality of human resources through the development of competitive education and health is a strategic issue in RPJMD of Sulawesi Utara Province 2016-2021. Characteristics of the Sulawesi Utara Province, which consists of several islands with different regional typologies led to the need for classification of the area so that development programs can be optimized. The social-economic indicators that used for regional classification in Sulawesi Utara are the HDI value, percentage of the poor, economic growth, and dependency ratio. The analysis used for the identification of the areas in this research is the analysis biplot and followed by one-way analysis Manova. Biplot analysis is used to illustrate the diversity of variables, the proximity between objects and the relationship variables in a two-dimensional graph. Manova analysis is used to determine significant differences between some variables in some groups. The results of this study show the formation of two groups of regions. The first group consists of Manado, Bitung, Tomohon, Kotamobagu, Minahasa and Minahasa Utara. This first group of regions is a district with high of HDI value, high economic growth, low poverty, and low dependency ratio. Keyword: biplot, classification, social-economic.